2018
DOI: 10.1080/16549716.2018.1434935
|View full text |Cite
|
Sign up to set email alerts
|

Improving access to medicines via the Health Impact Fund in India: a stakeholder analysis

Abstract: Background: In India, 50–65% of the population face difficulties in accessing medicines. The Health Impact Fund (HIF) is a novel proposal whereby pharmaceutical companies would be paid based on the measured global health impact of their drugs. We conducted a key stakeholder analysis to explore access to medicines in India, acceptability of the HIF and potential barriers and facilitators at policy level. Objectives: To conduct a stakeholder analysis of the HIF in India: to determine key stakeholder views regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
1
0
1
Order By: Relevance
“…This study demonstrated that decision-making on cutting the foreign currency subsidies has a long history of debate that requires the participation of all stakeholders to reach consensus. Policies to improve access to medicines should be multisectoral and need to engage different stakeholders to achieve maximum support [ 59 ]. The study also revealed that an important challenge in allocating foreign currency subsidies is the dominance of a top-down approach in formulating and implementing policies, which affects the relationships between actors.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that decision-making on cutting the foreign currency subsidies has a long history of debate that requires the participation of all stakeholders to reach consensus. Policies to improve access to medicines should be multisectoral and need to engage different stakeholders to achieve maximum support [ 59 ]. The study also revealed that an important challenge in allocating foreign currency subsidies is the dominance of a top-down approach in formulating and implementing policies, which affects the relationships between actors.…”
Section: Discussionmentioning
confidence: 99%
“…Джерело: розроблено на основі [8] Таким чином на рис. 1 показано, що проблема відтоку висококваліфікованих працівників з державного сектору у приватний пов'язана з поширенням неефективного механізму управління фінансовими ресурсами у галузі охорони здоров'я.…”
Section: рис 1 методика 5 «чому?» у процесі управління ризикамиunclassified